2020
DOI: 10.1093/plphys/kiaa019
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal gibberellin biosynthesis is carbon dependent and adjusts leaf expansion rates to variable conditions

Abstract: Optimal plant growth performance requires that the presence and action of growth signals, such as gibberellins (GAs), are coordinated with the availability of photo-assimilates. Here, we studied the links between GA biosynthesis and carbon availability, and the subsequent effects on growth. We established that carbon availability, light and dark cues, and the circadian clock ensure the timing and magnitude of GA biosynthesis and that disruption of these factors results in reduced GA levels and expression of do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…One mechanism that aids such a safety lock is the sugar-mediated repression of miR156 [26,27]. Another is the sugar-dependent regulation of GA biosynthesis [119], which also stimulates phase transitions to adulthood and reproduction [49].…”
Section: Morphological Plasticitymentioning
confidence: 99%
“…One mechanism that aids such a safety lock is the sugar-mediated repression of miR156 [26,27]. Another is the sugar-dependent regulation of GA biosynthesis [119], which also stimulates phase transitions to adulthood and reproduction [49].…”
Section: Morphological Plasticitymentioning
confidence: 99%
“…Seeds were germinated on ½ MS control media, transferred after one day to either control or GA-containing ½ MS media (Supplemental Figure 1A), and transferred after four days to new plates (van Gelderen et al, 2018). We used the GA4 form of Gibberellic acid, since it is a more prevalent bioactive form in Arabidopsis than the often used GA3 (Prasetyaningrum et al, 2020), with a good affinity to the gibberellin sensor GID1 (Yoshida et al, 2018). However, we compared its effect against that of GA3, which confirmed that GA4 is a more potent gibberellin than GA3 (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A longer photoperiod enhances GA biosynthesis, resulting in a higher expression of the key GA synthesis genes GA20ox and GA3ox , consequently inducing active GAs in Arabidopsis [ 62 ]. In contrast, a lower light availability reduced the expression of GA20ox and GA3ox , resulting in reduced leaf expansion [ 63 , 64 ] and demonstrating that GA20ox and GA3ox are dependent on the intensity and quality of light in Rosa sp. [ 37 ].…”
Section: Gas Regulate Leaf Developmentmentioning
confidence: 99%